DAYA SAING EKSPOR KOMODITAS KELAPA INDONESIA TERHADAP TIGA NEGARA DI ASIA - Ineke Nursih Widyantari (AGRICOLA, 2013)
Indonesia has an area of widest coconut and its products is high ranking in the world. However, Indonesia is still exporting coconut in crude form, processing is not as much as other countries such as the Philippines. This study aims to determine the level of coconut export commodities competitive in Indonesia. This research using the method of  RCA (Revealed Comparative Advantage) and CEP (Comparative Export Performance) Index. The results of this study based on the RCA method indicate that Indonesia coconut commodity export during the period 2006 - 2010 is larger than 1. Based on the CEP method Indonesia indicate that during the period 2006-2008 is greater than 1 and during the period 2009-2010 is smaller than 1. Indonesian have competitiveness and decreased from specialized be not specialized.